Comparison Between Crystalline Morphology of Isotactic Polypropylene with Di-p-methylbenzylidene Sorbitol and Sodium Benzoate - HAO, WENTAO; YANG, WEN (Asian Journal of Chemistry, 2010)
Isothermal crystalline morphology of isotactic polypropylene (iPP) with di-p-methylbenzylidene sorbitol (Me-DBS), a clarifying nucleating agent, under different crystallization conditions was observed and compared with that of iPP containing sodium benzoate (SB). The results showed that the crystalline morphology of iPP/Me-DBS and iPP/SB were much different. It was concluded that the crystallization mechanism of Me-DBS was not simply the heterogeneous nucleation, but to provide small amount of growth points, on which iPP segments could attach and grow effectively.